The Effects of Transcription Directions of Transgenes and the gypsy Insulators on the Transcript Levels of Transgenes in Transgenic Arabidopsis. Issue 1 (December 2017) - Jiang, Weijia; Sun, Li; Yang, Xiaojie; Wang, Maohua; Esmaeili, Nardana; Pehlivan, Necla; Zhao, Rongli; Zhang, Hong; Zhao, Yun
Abstract Manipulation of a single abiotic stress-related gene could improve plant performance under abiotic stress conditions. To simultaneously increase plant tolerance to multiple stresses, it is usually required to overexpress two (or more) genes in transgenic plants. The common strategy is to assemble two or more expression cassettes, where each gene has its own promoter and terminator, within the same T-DNA. Does the arrangement of the two expression cassettes affect expression of the two transgenes? Can we use the Drosophilagypsy insulator sequence to increase the expression of the two transgenes? Answers to these questions would contribute to design better transformation vectors to maximize the effects of multi-gene transformation. Two Arabidopsis genes, PP2A-C5 andAVP1, and thegypsy insulator sequence were used to construct six transformation vectors with or without thegypsy insulator bracketing the two expression cassettes: uni-directional transcription, divergent transcription, and convergent transcription. Total RNAs were isolated for reverse transcription- quantitative real-time polymerase chain reaction (RT-qPCR) assays and a thorough statistical analysis was conducted for the RT-qPCR data. The results showed that thegypsy insulator does promote the expression of two transgenes in transgenic plants. Besides, the plants containing the divergent transcription cassettes tend to have more correlated expression of both genes.